Role of two co-occurring Mediterranean sea urchins in the formation of barren from Cystoseira canopy. (5th January 2015) - Agnetta, D.; Badalamenti, F.; Ceccherelli, G.; Di Trapani, F.; Bonaviri, C.; Gianguzza, P.
Abstract: In the Mediterranean Sea the co-occurring sea urchins Paracentrotus lividus and Arbacia lixula are usually considered to share the same ecological role in the formation of barren from Cystoseira canopy. However, their foraging ability may vary due to feeding behavior and species-specific morphological traits. The relative effects of P. lividus and A. lixula on Cystoseira canopy was tested experimentally both in the laboratory, at a density of about 20 ind./m 2, and in the field by gut content analysis. Field and laboratory results show that A. lixula is unable to affect Cystoseira spp. Furthermore, these results confirmed the great ability of P. lividus to consume Cystoseira canopy, thus supporting the evidence of the major role of this species in the creation of a barren state.